FIELD GEOLOGY OF SOME GRANITIC ROCKS IN THE KALTUNGO AREA, NORTHEASTERN NIGERIA - Rufai, Fauziya Ahmed; Halilu, Maimuna (IJRDO-Journal of Applied Science, 2017)
Granitic rocks of the Kaltungo Inlier were assessed in a view to glean more information abouttheir origin. The area comprised of coarse granied porphyritic granite, pegmatite and diorite.The tectonic structures in the study area trend mostly NE – SW and subordinately NW-SEand N-S conform with the regional deformational structures which occurred during the PanAfrican thermotectonic events in the Nigerian basement.